Interaction between an edge dislocation and a rigid hypotrochoidal inhomogeneity - Wang, X.; Schiavone, P. (Archives of Mechanics, 2024)
We study the plane elasticity problem associated with a rigid hypotrochoidal inhomogeneity embedded in an infinite isotropic elastic matrix subjected to an edge dislocation located at an arbitrary position. A closed-form solution to the problem is derived primarily with the aid of conformal mapping and analytic continuation. All of the unknown complex constants appearing in the pair of analytic functions characterizing the elastic field in the matrix are determined in an analytical manner. In addition, a simple method distinct from that by Santare and Keer (1986) is proposed to determine the rigid body rotation of the rigid inhomogeneity.